Effects of ɷ - 3 Fatty Acids on Liver Function Tests in Patients with Diabetes Mellitus - Habib, Tamanna Binte; Akhter, Qazi Shamima; Imam, Hasan; Yeasmin, Nahid (Medicine Today, 2020)
Introduction: Patients with type-2 Diabetes are augmented the risk of non alchoholic fatty liver disease that rises liver enzymes and total protein.To observe the favourable effects of fish oil capsule on liver function tests in patients with type 2 DM. Materials and Methods: A prospective interventional study was conducted from January 2017 to December 2017. A total numbers of 52 diagnosed type 2 diabetic patients of both sexes were scrutinized with age ranging from 40 to 50 years. Among them, 27 type 2 diabetic patients those who taken oral fish oil gel (2g/day) for 12 weeks were preferred as study group. Another 25 type 2 diabetic patients without supplementation of omega 3 fatty acid were nominated as control group for comparison. The study subjects were selected from Dhaka Medical College Hospital, Dhaka and personal contact from Dhaka city on the basis of criteria. The research work was administrated with ethical clearance from concerned authority. Results: In this study ALP, LDH, total protein were reduced in diabetic patients after supplementation with omega-3 fatty acid in comparison to that of their baseline value. Again, after 12 weeks, ALP (Alkaline Phosphatase) LDH (Lctate dehydrogenase) and total protein were decreased in diabetic patients after supplementation with omega-3 fatty acid in comparison to control group. Conclusion: After analyzing the results of the study, it can be concluded that omega-3 fatty acid can reduce ALP, LDH and total protein levels in diabetic patients may be helpful to minimize the risk of fatty liver in type-2 diabetes mellitus. Medicine Today 2020 Vol.32(2): 91-94